2004
DOI: 10.1016/j.cellbi.2003.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overexpression of the integral membrane protein Itm2A enhances myogenic differentiation of C2C12 cells

Abstract: Integral membrane protein 2A (Itm2A) is a transmembrane protein belonging to a family composed of at least two other members, Itm2B and Itm2C, all of them having a different expression pattern. The protein serves as a marker for early stages in chondrogenesis and T-cell development. Itm2A is also highly expressed in skeletal muscle. In order to understand the role of Itm2A in muscle development, we constitutively overexpressed exogenous Itm2A in C2C12 myoblast cells. Several clones expressing high levels of It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Immunohistochemical analysis of the CBFb-MYH11 protein revealed a unique nuclear localization in our M4Eo cases. 19 ITM2A, a novel type II integral membrane protein gene that is involved in T-cell development and Comparative analysis of genes in acute myeloid leukemia M4Eo X Sun et al activation, 20 myogenesis, 21 and chondrogenesis 22 was a good marker of M4Eo in this study. The expression levels of ITM2A were higher in all 18 M4Eo cases in the cDNA microarray ( þ 3.41-fold; Table 2a).…”
Section: M4eo Has a Distinct Gene Expression Profilementioning
confidence: 93%
“…Immunohistochemical analysis of the CBFb-MYH11 protein revealed a unique nuclear localization in our M4Eo cases. 19 ITM2A, a novel type II integral membrane protein gene that is involved in T-cell development and Comparative analysis of genes in acute myeloid leukemia M4Eo X Sun et al activation, 20 myogenesis, 21 and chondrogenesis 22 was a good marker of M4Eo in this study. The expression levels of ITM2A were higher in all 18 M4Eo cases in the cDNA microarray ( þ 3.41-fold; Table 2a).…”
Section: M4eo Has a Distinct Gene Expression Profilementioning
confidence: 93%
“…Although the roles and association of these genes with AS have not yet been reported, ITM2A is involved in osteoand chondrogenic cellular differentiation (cells responsible for the development of bone and cartilage, respectively) (Deleersnijder et al, 1996). ITM2A is also involved in the activation of T cells in the immune system (Kirchner and Bevan, 1999) and in myocyte differentiation (Van den Plas and Merregaert, 2004). Furthermore, some of the upregulated genes, e.g., ITM2A and collagen, type IX, alpha 2 (COL9A2), might modulate cartilage and bone metabolism leading to AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…16 While ITM2A expression enhances myogenic differentiation of C2C12 cells, forced ITM2A expression inhibits chondrogenic differentiation of mesenchymal stem cells. 17,18 In addition, a recent report showed that ITM2A expression is regulated by the transcription factor GATA3, which is expressed exclusively in the T cell lineage. ITM2A overexpression in mouse T cells partially suppresses CD8 expression suggesting ITM2A is involved in T cell development.…”
Section: Introductionmentioning
confidence: 99%